Sexual Spousal Abuse And Emotional Homeostatic Disequilibrium (EHD) Among Married Secondary School Teachers In Rivers State, Nigeria - Musah, Ebikabowei (Academic Journal of Psychology and Counseling, 2024)
This study considered the phenomenon of emotional homeostatic disequilibrium (EHD) that adversely affects individuals, to unveil factors that instigate it. It was carried out in the area of counseling psychology. The purpose was to determine whether or not sexual spousal abuse is related to EHD among married secondary school teachers in Rivers State of Nigeria (N=766). This quantitative study adopted an expost facto correlation design, while two research questions and two null hypotheses guided the study. Results of the study indicated a significant relationship between sexual spousal abuse and EHD (F = 98.01, r = 0.58, p < 0.05), and a moderating influence of cultural values/beliefs in that relationship among the participants (F=53.617, p<0.05). Specifically, this study contributes to a deeper understanding of the psychological and emotional toll of sexual spousal abuse and informs more effective support and intervention strategies.